PRAPEMANASAN MENINGKATKAN KERENYAHAN KERIPIK SINGKONG DAN UBI JALAR UNGU - - Rosanna; Yonas Octora; Adil Basuki Ahza; Dahrul Syah (Jurnal Teknologi dan Industri Pangan, 2015)
Crispness as one of the important parameters for chips quality wants to be pursued. In this research, heat treatments before frying, such as steaming and boiling, were expected can help preparing the porous structure in the chips material before frying through the gelatinization mechanism. The porous structure is an important factor in crispness. Raw materials used were tuber crops, such as cassava and purple sweet potato. The aims of this study were to determine the effect of the heat treatments before frying on the chips crispness and obtain the heating process temperature and time that could produce chips with the best crispness. Chips crispness was analyzed using a rating test as organoleptic test and texture analyzer as physical test. Cassava and purple sweet potato slices steaming and boiling treatments before frying increased the chips crispness (P<0.05). Steaming of cassava slices for 5 minutes at a temperature of 100°C or boiling them for 3 minutes at a temperature of 95°C and steaming of purple sweet potato for 3 minutes at a temperature of 100°C or boiling them for 1.5 minutes at a temperature of 95°C before frying became the best time to improve the chips crispness organoleptically and physically compared with control. The treated cassava chips water and fat content changes didn’t affect their crispness.